ANALYSIS OF THE IMPLEMENTATION OF MERDEKA CURRICULUM ON ANTI-CORRUPTION EDUCATION - Sutanto, Sutanto; Darmuki, Agus; W, Sri Surachmi; Ismaya, Erik Aditia (Universitas Muria Kudus, 2024)
This study aims to analyze the implementation of Merdeka Curriculum in supporting anti-corruption education at SD Negeri 1 Pulongrambe, Tawangharjo District. The research method used is narrative qualitative with a descriptive approach. Data were collected through in-depth interviews, observation, and document analysis. The results showed that the implementation of Merdeka Curriculum provides flexibility for teachers to integrate anti-corruption values in learning activities. This finding provides new insights into the effectiveness of the Merdeka Curriculum in shaping students character with integrity. The conclusion of this study emphasizes the importance of policy support and teacher training in implementing anti-corruption education.